STRATEGI COPING DAN KEBAHAGIAAN ISTRI DALAM PERKAWINAN POLIGAMI - Hanoum, Magdalena (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2014)
Polygamy is a marriage problem that most widely debated and be a controversy. The problems that arise in polygamous marriage could be related to various aspects, including physical, psychological, and also social aspects. Nevertheless, several studies indicated that polygamous marriage could be successful if each party in the family gives a positive judgment to those polygamous marriage itself, and willing to do coping to the situations that could be considered as a stressor. By coping, each individuals in the family would be able to live a good life with a polygamous marriage, and happy, without a conflict that might be end in a divorce.The aim of this study is to determine whether there is a correlation between using stress coping strategies and the level of happiness of the wife in polygamous marriage, whether there are differences in the level of happiness to the wife to use different coping strategies. The samples selection is done based on the purposes of the research (purposive sampling), whom are the wives of a polygamous marriage. The resulting data of the research is formed in an interval data, so be analyzed with a pearson product moment correlation. Then comparative analysis using one-way anova